THE THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY (CSR) ON COMPANY VALUES WITH COMPANY PROFITABILITY AS MODERATING VARIABLES IN PLANTATION COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Dwinata, Andru (International Journal of Public Budgeting, Accounting and Finance, 2020)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) in terms of labor disclosure, product responsibility, economic performance, environment, and waste on firm value with profitability as a moderating variable on plantation companies on the IDX. This type of research is causal associative research. The research method uses secondary data collection techniques. The population in this study included plantation companies listed on the Indonesia Stock Exchange from 2013 to 2017. The sampling method used in this study was purposive sampling. Data were processed using panel data regression analysis. The results showed that the workforce had a negative and not significant effect on firm value. Product liability has a positive and significant effect on firm value. Economic performance has a positive and not significant effect on firm value. Energy has a positive and not significant effect on firm value. Waste has a negative effect and is not significant to the firm value. Profitability is a moderating variable for the relationship between labor, product responsibility, and waste on firm value. But the profitability variable is not a moderating variable for the relationship between economic performance and energy on firm value.